Investigation of the Composition of High-Viscosity and Heavy Oils in the Course of EOR-Process Simulation; Журнал Сибирского федерального университета. Серия: Химия; Т. 10, № 2 - Chuikina D. I. Darya; Russkikh I. V. Irina; Stakhina L. D. Larisa; Serebrennikova O. V. Olga Viktorovna (2017, 2017)
Title screen